2000
DOI: 10.4049/jimmunol.164.11.5583
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Lymphocyte Activation Gene-3 Molecule Used as a Vaccine Adjuvant Elicits Greater Humoral and Cellular Immune Responses to Both Particulate and Soluble Antigens

Abstract: The lymphocyte activation gene-3 (LAG-3) product is a MHC class II ligand that has been used in vivo to stimulate MHC class II+ APCs to increase tumor-specific immune responses. We investigated whether LAG-3 could also play an adjuvant role in vivo for the induction of humoral and CD4 or CD8 cell-mediated immune responses when immunizing mice with a particulate (hepatitis B surface Ag) or soluble (OVA) Ag. In both cases, coadministration of 1 μg of a soluble fusion protein between murine LAG-3 and the Fc fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…Finally we showed that LAG-3-transfected tumors in syngeneic mice completely regressed, or their growth was markedly reduced, which was in contrast to the aggressive growth of untransfected cells (30). We also showed that murine LAG-3Ig acts as an adjuvant for Th1 responses and cytotoxic T cell responses to proteinaceous Ags (31). Because murine T cells do not express class II, it seems likely that these responses are induced via a direct effect of LAG-3Ig on class II ϩ APC.…”
Section: Stimulation Of Cd8mentioning
confidence: 79%
See 1 more Smart Citation
“…Finally we showed that LAG-3-transfected tumors in syngeneic mice completely regressed, or their growth was markedly reduced, which was in contrast to the aggressive growth of untransfected cells (30). We also showed that murine LAG-3Ig acts as an adjuvant for Th1 responses and cytotoxic T cell responses to proteinaceous Ags (31). Because murine T cells do not express class II, it seems likely that these responses are induced via a direct effect of LAG-3Ig on class II ϩ APC.…”
Section: Stimulation Of Cd8mentioning
confidence: 79%
“…In previous studies LAG-3Ig was found to act as a vaccine adjuvant for the induction of T cell responses to nominal Ag in mice and to induce in vitro cytokine production by monocyte-derived human DC (31,36). To further analyze the role of LAG-3, monocyte-derived human DC cultured with IL-4 and GM-CSF for 6 days were incubated with soluble LAG-3Ig.…”
Section: Lag-3 Induces Morphological Changes In Immature DCmentioning
confidence: 99%
“…A soluble murine LAG-3-Ig fusion protein induced MHC class II mediated signaling in DC, leading to their activation and/or maturation as well as production of cytokines [19][20][21][22]. In addition, mLAG-3-Ig was shown to reduce tumor growth [23,24] and to increase CD8 cytotoxic responses and CD4 Th1 responses in mice [25].…”
Section: Introductionmentioning
confidence: 99%
“…ϩ Th cells and the cross-priming of CD8 ϩ CTLs (2,3,8). In mice, tumor rejection induced by LAG-3 was associated with induction of tumor-specific CD8 cells (9,10) and presence of CD86-expressing APCs, NK cells, granulocytes, and infiltrating T cells as well as production of IFN-␥, CCL2/MCP-1, and CCL5/RANTES at the tumor site (11).…”
mentioning
confidence: 99%